2011
DOI: 10.1016/j.physa.2010.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks: Effect of subtle changes in nature of randomness

Abstract: In two different classes of network models, namely, the Watts Strogatz type and the Euclidean type, subtle changes have been introduced in the randomness. In the Watts Strogatz type network, rewiring has been done in different ways and although the qualitative results remain same, finite differences in the exponents are observed. In the Euclidean type networks, where at least one finite phase transition occurs, two models differing in a similar way have been considered. The results show a possible shift in one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The study made with much larger networks indicated that the network had finite dimensional behavior for 1 ≤ δ < 2 [45] while in [44], it was claimed that up to δ = 2, the small world behavior exists. In a more recent work [29], all possible shortest paths were evaluated numerically using a burning algorithm, and it was again found that the network retains the small world property up to δ = 2 while the clustering coefficient vanishes below δ = 1. Such a result was also obtained in [46].…”
Section: A Earlier Studies On This Network: Static Propertiesmentioning
confidence: 99%
“…The study made with much larger networks indicated that the network had finite dimensional behavior for 1 ≤ δ < 2 [45] while in [44], it was claimed that up to δ = 2, the small world behavior exists. In a more recent work [29], all possible shortest paths were evaluated numerically using a burning algorithm, and it was again found that the network retains the small world property up to δ = 2 while the clustering coefficient vanishes below δ = 1. Such a result was also obtained in [46].…”
Section: A Earlier Studies On This Network: Static Propertiesmentioning
confidence: 99%
“…Random model A is a variant of the WS model with identical static properties. It is regular for p = 0, random for p = 1, and for any p > 0, the nature of RMA is small-worldlike [13,16]. Euclidean models of RMB type have been studied in a few earlier works [16][17][18].…”
Section: Description Of the Network Modelsmentioning
confidence: 99%
“…It is regular for p = 0, random for p = 1, and for any p > 0, the nature of RMA is small-worldlike [13,16]. Euclidean models of RMB type have been studied in a few earlier works [16][17][18]. While it is more or less agreed that for α 1 the network is random and for α > 2 it behaves as a regular network, the nature of the network for intermediate values of α is not very well understood.…”
Section: Description Of the Network Modelsmentioning
confidence: 99%
“…The fact that results do not depend on the system size undermines our predictions that the average path length l itself determines if all mapping methods overlap or not, because the l increases with the system size [35]. However, one should probably not look at the path length itself but at the relative path length, which is defined as the average path length of a given network divided by the average path length of a random network of the same size and average degree.…”
Section: Resultsmentioning
confidence: 83%